Thinking Mathematically (6th Edition)

Published by Pearson
ISBN 10: 0321867327
ISBN 13: 978-0-32186-732-2

Chapter 6 - Algebra: Equations and Inequalities - 6.1 Algebraic Expressions and Formulas - Exercise Set 6.1: 57

Answer

-8$x^{2}$ + 10x

Work Step by Step

3(-4$x^{2}$ + 5x) - (5x - 4$x^{2}$) Use the distributive property to remove the parentheses =3.-4$x^{2}$ + 3.5x - (5x - 4$x^{2}$) Drop parentheses and change the sign of each term in parentheses: - (5x - 4$x^{2}$) = - 5x + 4$x^{2}$ = 3.-4$x^{2}$ + 3.5x - 5x + 4$x^{2}$ Multiply = -12$x^{2}$ + 15x - 5x + 4$x^{2}$ Group like terms = (-12$x^{2}$ + 4$x^{2}$) + (15x - 5x) combine like terms (-12$x^{2}$ + 4$x^{2}$) = (-12+4)$x^{2}$ = -8$x^{2}$, (15x - 5x) =(15 - 5)x = 10x =-8$x^{2}$ + 10x
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.